Identification of bacteria associated with Holothuria (Mertensiothuria) leucospilota from Pangkor Island - Muhammad Lutfi, Fatin Najihah; Mohamed Rehan, Maryam; Kamarudin, Kamarul Rahim; Che Zahri, Mohd Zulhafiz; Mohd Noor, Hanina; Mat Radzi, Salina (Malaysian Society of Applied Biology, 2018)
Holothuria (Mertensiothuria) leucospilota is the most abundant sea cucumber species in Malaysia. This study aimed to identify bacteria isolated from the external and internal body parts of H. leucospilota collected from the coastal water of Pangkor Island, Perak, Malaysia. A total of 26 bacterial samples were isolated using streak plate method from eight body parts of two fresh H. leucospilota specimens and from the surrounding surface sediments and seawater. Identification of the bacterial isolates was based on microscopic examination, 16S rDNA amplification and phylogenetic analysis using the neighbour-joining method. Three genera of bacteria were identified namely Vibrio, Bacillus, and Acinetobacter. The genus Vibrio was found to be the main bacterial group associated with the H. leucospilota specimens from Pangkor Island.